Penerapan Pemeliharaan Rumput Laut Sistem Semi Intensif Dengan Menerapkan Teknologi Keramba Apung Dengan Jaring Hampar Desa Pulau Lemukutan - Fitra Wira Hadinata; Putri Delilah Awaliyah; Oxy Ramadhani; Nabila Maulidia; Adi Imam Wahyudi; Hasan Eldin Adimu; Nikanor Hersal Armos (Yayasan Serumpun Karang Konservasi, 2024)
The number of seaweed cultivators on Lemukutan Island is increasing, this is because people who were previously fishermen are also interested in this business. There are more than 30 seaweed cultivators, the seaweed cultivation business is divided into several types of activities, namely seaweed maintenance, seaweed drying, seaweed processing and seaweed processing sellers. The seaweed cultivated is Eucheuma Cottonii with a production of around 30 tons/year. The results of seaweed production, seaweed drying and seaweed marketing have not been optimally carried out by the cultivator group because the problem is that the harvest results from seaweed cultivation are less than optimal due to the presence of pests in the form of turtles and rabbitfish which will cause the amount of seaweed production obtained. The solution offered to overcome this problem is training on the implementation of a semi-intensive system of seaweed maintenance using floating cage technology with overlay nets.